Long-read and chromosome-scale assembly of the hexaploid wheat genome achieves high resolution for research and breeding. (28th April 2022) - Aury, Jean-Marc; Engelen, Stefan; Istace, Benjamin; Monat, Cécile; Lasserre-Zuber, Pauline; Belser, Caroline; Cruaud, Corinne; Rimbert, Hélène; Leroy, Philippe; Arribat, Sandrine; Dufau, Isabelle; Bellec, Arnaud; et al.
Abstract: Background: The sequencing of the wheat ( Triticum aestivum ) genome has been a methodological challenge for many years owing to its large size (15.5 Gb), repeat content, and hexaploidy. Many initiatives aiming at obtaining a reference genome of cultivar Chinese Spring have been launched in the past years and it was achieved in 2018 as the result of a huge effort to combine short-read sequencing with many other resources. Reference-quality genome assemblies were then produced for other accessions, but the rapid evolution of sequencing technologies offers opportunities to reach high-quality standards at lower cost. Results: Here, we report on an optimized procedure based on long reads produced on the Oxford Nanopore Technology PromethION device to assemble the genome of the French bread wheat cultivar Renan. Conclusions: We provide the most contiguous chromosome-scale assembly of a bread wheat genome to date. Coupled with an annotation based on RNA-sequencing data, this resource will be valuable for the crop community and will facilitate the rapid selection of agronomically important traits. We also provide a framework to generate high-quality assemblies of complex genomes using ONT.